THE INTELLIGENCE CONDITIONING FOR EX-TERRORISM CONVICTS TO PREVENT RADICALISM AND TERRORISM IN NORTH SUMATERA - Pardede, Satya Dharma (Jurnal Pertahanan dan Bela Negara, 2020)
The Agency of National Counterterrorism (BNPT) is an institution that is concerned about terrorism as a result of radicalism. Based on information from the BNPT, of the approximately 600 ex-convict terrorist who have been released, some of them have returned to committing acts of terrorism. This is of particular concern to the security apparatus, particularly the National Intelligence Agency (BIN), the Indonesian National Armed Forces (TNI) and the Indonesian National Police (Polri), in preventing acts of terrorism. In addition, several areas have become locations for the realization of acts of terrorism, one of them is in the province of North Sumatera. This research aims to analyze and describe the intelligence conditioning activities for ex-terrorism convicts (Napiter) by related parties in preventing the spread of radicalism that leads to acts of terrorism in North Sumatera. The method used in this research is the theory of intelligence conditioning approaches, deradicalization theory, and synergies theory. Data was collected through interviews and observations, then was analyzed using NVIVO as a tool to categorize and make it easier to describe problems and draw conclusions. The results showed that intelligence conditioning for ex-convict terrorists have collaborated with several parties in the implementation of State Intelligence in the regions, including the BIN, TNI, Polri, and the regional government. In its implementation, terror convicts are given counseling and socialization related to nationalism, national insight, religion, and entrepreneurship. These activities are carried out while in the Correctional Institution (LP) by the LP and the police as well as after leaving the prison with monitoring from BIN, TNI, Polri, and regional governments. Besides, the process of intelligence conditioning when ex-convict terrorists are free will still have special attention through hospitality to terror convictions with persuasive communication by local officials. Furthermore, they are also given entrepreneurship assistance and independent business by local governments, as well as socialization related to the dangers of hoaxes in the digital world either from gadgets or other media. BNPT has fundamentally implemented deradicalization by synergizing all parties from other institutions. Based on the activities that have been carried out, it becomes a consideration and a concrete example that intelligence conditioning can prevent the spread of radicalism and acts of terrorism in society. Keywords: Ex-Terrorism Convicts, Intelligence Conditioning, Radicalism, Terrorism